PENGARUH MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI GIMKIT TERHADAP MINAT BELAJAR SISWA DALAM MATA PELAJARAN EKONOMI - Kharisma Aulia Maharani; Putri Ulfa Kamalia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The low interest of students in learning economics due to the use of monotonous and one-way Power Point Text media is the background of this research. The main focus of the research is to test the effect of Gimkit educational game-based learning media on students' interest in learning. This research uses a quantitative approach with a quasi-experimental method in the form of a non-equivalent control group design. The sample was selected through a purposive sampling technique that designated class X-A as the experimental group and class X-C as the control group at SMAN 10 Surabaya. Important research stages include administering a pretest, implementing treatment using the Virtual Economy feature on the material of Market Price Formation, completing a posttest questionnaire, and class observation. Quantitative findings from the Independent Samples t-test showed a significance value of 0.000 <0.05, which proves a significant difference in average learning interest between groups. The experimental class experienced an increase in the average posttest score of 11.06 (from 48.27 to 59.33), much higher than the control class which only increased by 1.06. Furthermore, the experimental group's N-Gain test reached 33.36% (medium category) compared to the control group's 2.90% (low category). The main conclusion of the study confirms that the use of Gimkit significantly increased students' interest in learning economics. The synergy of virtual economics features proved effective in transforming students' passive roles into active ones, in line with constructivist theory. ABSTRAK Rendahnya minat belajar siswa pada mata pelajaran ekonomi akibat penggunaan media Power Point Teks yang monoton dan searah melatarbelakangi penelitian ini. Fokus utama riset adalah menguji pengaruh media pembelajaran berbasis game edukasi Gimkit terhadap minat belajar siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan metode kuasi eksperimen berbentuk non-equivalent control group design. Sampel dipilih melalui teknik purposive sampling yang menetapkan kelas X-A sebagai kelompok eksperimen dan kelas X-C sebagai kelompok kontrol di SMAN 10 Surabaya. Tahapan penelitian penting meliputi pemberian pretest, pelaksanaan perlakuan dengan memanfaatkan fitur Virtual Economy pada materi Terbentuknya Harga Pasar, pengisian kuesioner posttest, serta observasi kelas. Temuan kuantitatif hasil uji Independent Samples t-test menunjukkan nilai signifikansi sebesar 0,000 < 0,05, yang membuktikan adanya perbedaan rata-rata minat belajar yang nyata antar kelompok. Kelas eksperimen mengalami peningkatan skor rata-rata posttest sebesar 11,06 (dari 48,27 menjadi 59,33), jauh lebih tinggi dibandingkan kelas kontrol yang hanya naik 1,06. Selain itu, uji N-Gain kelompok eksperimen mencapai 33,36% (kategori sedang) dibandingkan kelas kontrol sebesar 2,90%(kategori rendah). Simpulan utama penelitian menegaskan bahwa penggunaan Gimkit berpengaruh signifikan dalam meningkatkan minat belajar ekonomi siswa. Sinergi fitur ekonomi virtual terbukti efektif mengubah peran pasif siswa menjadi aktif sesuai teori konstruktivisme.